STRATEGI BAURAN PEMASARAN AIR MINERAL HK DIKABUPATEN FAKFAK - Sriwijaya, Reski Rahman; Atirah; Tuturop, Ivana Meisiyo (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
Engaged in the industrial sector to meet the needs of the majority of society. The HK Mineral Water Industry was founded in 2011 until now. The marketing mix in the HK mineral water business is already good enough so that the marketing process with the 4P concept applied can run according to the market conditions at the sales location. The purpose of writing the Assignment report The end is to find out the marketing mix strategy for HK Mineral Water by the HK Mineral Water business in Fakfak district. The author uses a descriptive analysis method that compares existing data with various theories that support existing data with various theories that support and are explanatory and expounding. Measurement of variables This is done using the Libert scale, which is used for the attitudes, opinions and perceptions of a person or group of people. This research involved 50 respondents from the population of HK mineral water consumers in the city of Fakfak. The questionnaires distributed have all been distributed and can be used as data in this research. Regarding Air HK product quality, regarding the packaging of Air HK products it is in the good category. A product is anything that a producer can offer to the market to fulfill the market's desires or needs to fulfill desire or need. In this research, the implementation of the marketing strategy used by HK Mineral Water is quite good because it always focuses on fulfilling the needs and desires of consumers. From the results of the research carried out, it can be concluded that the research results are the marketing mix strategy for HK Mineral Water in Fakfak district from all product variables with respondents who said that the Air Mineral HK product was in the good category with 1559 points, it could be concluded that the Air HK product was running well. Keywords: Water, Marketing Mix Strategy, Fakfak Regency